The mandatory adoption of IFRS and earnings quality: the moderating effect of family firms in Jordan - Al-shyoukh, Fayis Mahmoud Rasheed (2020)
Earnings quality of Jordanian public listed firms needs significant improvement due to poor accounting practices and lack of internal governance mechanism, therefore regulators have taken initiative to implement IFRS. This study aims to examine whether earnings quality (value relevance, timely loss recognition, earnings persistence, earnings management) has improved post-IFRS adoption in Jordan. It also aims to examine whether the effect of IFRS on earnings quality is moderated by family firms to address significant gap in literature. Data covering fifteen years 2001-2003 as pre-IFRS adoption and 2004-2015 as post-IFRS adoption were obtained from the annual reports of Jordanian listed industrial and service sector firms. Findings show that IFRS do not influence value relevance of book value of equity, whereas, the value relevance of earnings is higher after the IFRS adoption under return model only. Timely loss recognition is significantly lower, earnings persistence is significantly higher and earnings management is insignificantly lower after IFRS adoption. The family firms are not a moderator on effect of IFRS on value relevance of book value of equity, whereas, family firms are a moderator on effect of IFRS on value relevance of earnings based on the return model only. Family firms are a moderator on effect of IFRS on timely loss recognition and a moderator on effect of IFRS on earnings persistence. Finally, family firms are not a moderator on the effect of IFRS on earnings management. Overall, there are mixed findings regarding the impact of IFRS adoption and family firms on different measures of earnings quality pre and post-IFRS adoption periods. This study contributes to agency theory by claiming that risk of type 2 agency conflict is somehow lower in family firms after the IFRS adoption that trigger regulators to promote closely held firms to improve IFRS adoption and earnings quality.